Pendidikan Karakter Kepedulian Berdasarkan Al-Qur’an - Nayla Yasmina Fajri (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to uncover the concept of compassion in the Qur'an and analyze its role in character development, particularly in character education in the contemporary era, which faces the challenges of individualism and the decline of social values. Using a thematic interpretation approach (tafsīr mauḍū‘ī) and a qualitative method based on library research, this study explores the values of compassion, such as empathy, solidarity, and social responsibility, through an analysis of Qur'anic verses. The findings reveal that the values of compassion in the Qur'an encompass spiritual, social, and environmental dimensions, which can be implemented in various aspects of education, including formal, non-formal, and informal settings. Values such as charity (ṣadaqah), almsgiving (zakāh), mutual assistance, and environmental conservation are recommended to be integrated into the education curriculum. The conclusion emphasizes that character education based on Qur'anic values significantly contributes to shaping individuals who are not only intellectually excellent but also empathetic and morally responsible. This study recommends strengthening collaboration between families, schools, and communities to support the implementation of compassionate values, as well as utilizing digital technology to broaden the reach of Qur'an-based character education.